A method for preparing coating based on fluorescence-induced corrosion
By using modified microcapsules and fluorescent materials in anticorrosion coatings, combined with the pH sensitivity of anthocyanins, the problem of ineffective warning of corrosion in the prior art is solved, and the double warning of metal corrosion and the weather resistance of the coating is achieved. .
Patent Information
- Application Number
- CN202410802724.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-20
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-06-20
AI Technical Summary
Existing anticorrosion coatings cannot effectively warn of local environmental pH changes and the increase in metal ion content after corrosion, and the stability and weather resistance of fluorescent materials and pH indicators are poor.
Using a coating preparation method based on fluorescence sensing, microcapsules with modified fluorescent materials and anthocyanins are prepared by combining epoxy resin, modified microcapsules, silane coupling agent, dispersant and thixotropic agent, and microcapsules with modified fluorescence. Materials and anthocyanins achieve fluorescence or color changes under different pH conditions, provide double warnings, and improve the stability of fluorescent materials through modification treatment.
It realizes a double warning of metal corrosion, improves the weather resistance and stability of anticorrosive coatings, can effectively detect metal ions and maintain high-efficiency performance under different environmental conditions.
Smart Images

Figure BDA0004903835490000031 
Figure BDA0004903835490000041 
Figure BDA0004903835490000051
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a method for preparing coatings based on fluorescence-induced corrosion. Background Art
[0002] Metals, as indispensable materials in production and life, play an irreplaceable role. However, when metal materials come into contact with surrounding media during use, they will be damaged by chemical and electrochemical reactions, causing metal corrosion. Metal corrosion can cause equipment damage, pipeline leakage, product pollution and other phenomena, seriously affecting the development of people's production and life. Heavy anti-corrosion coatings have been used in many newly built industrial buildings, highway bridges, trains and ships, marine engineering and industrial pipelines to reduce the occurrence of corrosion.
[0003] When exposed to natural light, fluorescent materials can absorb part of the light energy, excite photons and release them in the form of visible light. However, fluorescent powder coatings have disadvantages such as poor weather resistance and poor thermal stability, which limit the application of fluorescent powder coatings in anti-corrosion coatings.
[0004] Patent application CN107793817A discloses a method for preparing a fluorescent coating doped with organic-inorganic composite fluorescent montmorillonite, wherein the fluorescent coating comprises bisphenol A epoxy resin, a curing agent and organic-inorganic composite fluorescent montmorillonite, etc. However, the fluorescent properties of the fluorescent substances are relatively weak and the sensitivity is not high;
[0005] Patent application CN112354493A discloses a method for preparing pH sensitive microcapsules, which uses pH sensitive silica gel as a core material to prepare sensitive microcapsules with a composite structure. However, the above-mentioned sensitive microcapsules only have an obvious indication effect on changes in pH value, and cannot serve as a warning for changes in metal ion concentration after corrosion of the metal substrate.
[0006] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing a coating based on fluorescence-induced corrosion, which is used to solve the problem that the anti-corrosion coating applied to metal materials in the prior art fails to provide double warning of corrosion phenomena by emitting fluorescence or color changes in response to changes in the pH value of the local environment and the increase in the metal ion content after corrosion. In addition, the fluorescent materials and pH indicators in the anti-corrosion coatings also have technical problems of poor stability and poor weather resistance.
[0008] The purpose of the present invention can be achieved by the following technical solution: A method for preparing a coating based on fluorescence-induced corrosion, comprising the following steps:
[0009] S1, epoxy resin, modified microcapsules, silane coupling agent, dispersant and thixotropic agent are uniformly mixed to obtain component A;
[0010] S2, epoxy resin curing agent and active diluent are mixed evenly, and then pigments and fillers are added and dispersed evenly at high speed to obtain component B; component A is added to component B and dispersed evenly to obtain a coating based on fluorescent induction corrosion.
[0011] The fluorescent induction corrosion-resistant coating designed by the present invention is specifically an epoxy anti-corrosion coating, which consists of component A and component B; component A includes epoxy resin, modified microcapsules, silane coupling agent, dispersant and pigments and fillers, and component B includes epoxy resin curing agent, active diluent and pigments and fillers.
[0012] Furthermore, the preparation method of the modified microcapsule comprises the following steps:
[0013] A1. Evenly mix the modified fluorescent material, anthocyanin, Span85 and deionized water, and stir at 50-60° C. for 10-20 min to obtain a mixed solution; ultrasonically emulsify the mixed solution to obtain a core material emulsion;
[0014] A2, β-cyclodextrin, gum arabic and deionized water are mixed uniformly to obtain a mixed solution; the mixed solution is magnetically stirred at 70-80° C. and 300-500 rpm until the mixed solution becomes transparent to obtain a wall material solution;
[0015] A3. The wall material solution is added drop by drop into the core material emulsion, uniformly dispersed under a high-speed dispersing homogenizer, and then allowed to stand for defoaming to obtain a mixed solution; the mixed solution is spray dried to obtain modified microcapsules.
[0016] Under the action of emulsifier, modified fluorescent material and anthocyanin are used as core materials to prepare core material emulsion; β-cyclodextrin and gum arabic are used as wall materials to prepare wall material solution. The core material emulsion is then dispersed in the wall material solution, and the mixed liquid is atomized in the high-temperature airflow, so that the deionized water that dissolves the wall material evaporates rapidly, thereby solidifying the wall material and finally microencapsulating the core material.
[0017] Furthermore, in step A1, the usage ratio of the modified fluorescent material, anthocyanin, Span85 and deionized water is 10-20 g: 5-10 g: 0.2-0.5 g: 20 mL; the power of ultrasonic emulsification is 30-50 W, and the duration of ultrasonic emulsification is 10-20 min.
[0018] Furthermore, in step A2, the dosage ratio of β-cyclodextrin, gum arabic and deionized water is 5g:5g:20mL; in step A3, the dosage ratio of wall material solution and core material emulsion is 20-30mL:10mL; the inlet air temperature of spray drying is 180-200°C and the wind speed is 100-120m3 / h.
[0019] Furthermore, in step A1, the preparation method of the modified fluorescent material comprises the following steps:
[0020] B1. Mix (4-aminophenyl)(phenyl)methanone [(4-aminophenyl)(phenyl)methylene]hydrazone, 4'-(4-formylphenyl)-2,2':6',2"-terpyridine and ethanol evenly, condense and reflux at 70-80°C and 100-300r / min for 4-5h, and filter while hot to obtain a modified solid; wash the modified solid alternately with ethanol and deionized water, and then vacuum dry to obtain intermediate A;
[0021] The reaction mechanism of (4-aminophenyl)(phenyl)methanone[(4-aminophenyl)(phenyl)methylene]hydrazone and 4'-(4-formylphenyl)-2,2':6',2"-terpyridine is as follows:
[0022]
[0023] The carbonyl group on 4'-(4-formylphenyl)-2,2':6',2"-terpyridine and the amino group on the raw material (4-aminophenyl)(phenyl)methanone [(4-aminophenyl)(phenyl)methylene]hydrazone undergo a nucleophilic substitution reaction, and a molecule of water is precipitated to obtain intermediate A; the larger the conjugated π bond of the intermediate A molecule, the greater the delocalization range of the electrons, so that it is easy to be excited into a high-energy excited state molecule, thereby improving the fluorescence intensity.
[0024] B2, intermediate A, and catalyst ferric chloride are mixed to obtain a reactant; chlorine gas is introduced into the reactant and mixed to react to obtain chlorinated intermediate A;
[0025] The reaction principle of intermediate A to prepare chlorinated intermediate A is as follows:
[0026]
[0027] B3, under nitrogen atmosphere, add anhydrous tetrahydrofuran to the chlorinated intermediate A, mix and stir evenly to obtain a mixed solid-liquid; n-butyl lithium and anhydrous DMF are added dropwise to the mixed solid-liquid, and the temperature is cooled to room temperature to obtain a reaction solution; saturated ammonium chloride solution is added to the reaction solution, extracted to obtain an organic phase; the organic phase is washed with saturated brine, dried over anhydrous sodium sulfate, and filtered to obtain intermediate B;
[0028] B4. In a 100mL four-necked round-bottom flask, add 30mL of ethanol solution, 1-2g of benzyl cyanide and 1.5-3g of potassium tert-butoxide, mix and stir at room temperature, then add 3-5g of intermediate B, mix and stir evenly to obtain a mixed solid-liquid; heat the mixed solid-liquid to 70-80°C and reflux for 3-4h, then cool to room temperature, separate and obtain an organic phase; use petroleum ether and ethyl acetate as solvents for elution of the organic phase to obtain a modified fluorescent material.
[0029] The invention comprises the following steps: chlorinating an intermediate A with multiple benzene ring groups, grafting halogens, and obtaining the intermediate A; using THF (tetrahydrofuran) as a solvent, dropping n-butyl lithium as a catalyst, and reacting the intermediate A with anhydrous DMF to obtain the intermediate B; and performing nucleophilic addition on the intermediate B and benzyl cyanide to obtain a modified fluorescent material with a cyano group.
[0030] The reaction principle of intermediate A for preparing modified fluorescent materials is as follows:
[0031]
[0032] Further, in step B1, the amount ratio of ((4-aminophenyl)(phenyl)methanone[(4-aminophenyl)(phenyl)methylene]hydrazone, 4'-(4-formylphenyl)-2,2':6',2"-terpyridine and ethanol is 15-20g:15-25g:300mL; the vacuum drying temperature is 70-80°C, and the vacuum drying time is 30-60min; in step B2, the amount ratio of intermediate A and catalyst ferric chloride is 20g:0.1-0.3g, the temperature of the mixed reaction is 60-70°C, and the mixing reaction time is 1-2h.
[0033] Furthermore, in step B3, the amount ratio of chlorinated intermediate A, anhydrous tetrahydrofuran, n-butyl lithium and anhydrous DMF is 10-15g:50-60mL:10-20mL:30-40mL; in step B4, the amount ratio of ethanol solution, benzyl cyanide, potassium tert-butoxide and intermediate B is 10-20mL:60mg:30mg:20-30mg.
[0034] Further, in step S1, the mass ratio of n-butanol to xylene is 1:1; in terms of parts, the mass ratio of epoxy resin, silane coupling agent KH-550 and modified microcapsules is 30:5-10g:30-40g; in terms of parts, in step S2, the usage ratio of epoxy resin curing agent, modifier, zinc phosphate and ferrophosphorus powder is 10-20:10-20:1-2:2-3. The mass ratio of epoxy resin to curing agent is 1:1.
[0035] Furthermore, in step S2, the epoxy resin is any one of epoxy resin E51 and epoxy resin E44; the dispersant is any one of ethyl bis stearamide, glyceryl stearate, and glyceryl tristearate; the thixotropic agent is any one of hydrogenated castor oil and polyvinyl alcohol; the epoxy resin curing agent is any one of epoxy curing agent T-31, epoxy curing agent 593, and epoxy curing agent K123; and the active diluent is cardanol glycidyl ether.
[0036] Furthermore, in parts by weight, the usage ratio of epoxy resin, modified microcapsules, silane coupling agent, dispersant and thixotropic agent is 50:10-20:1-2:0.1-0.5:1-1.5; in parts by weight, the usage ratio of epoxy resin curing agent, active diluent and pigments and fillers is 10-20:5-10:5-10; the pigments and fillers are zinc phosphate and ferrophosphorus powder, and in parts by weight, the usage ratio of zinc phosphate and ferrophosphorus powder is 1:1.
[0037] The present invention has the following beneficial effects:
[0038] 1. The coating based on fluorescence-induced corrosion prepared by the present invention is specifically an anti-corrosion coating, and its composition includes epoxy resin, modified microcapsules, silane coupling agent, dispersant, thixotropic agent, epoxy resin curing agent, diluent and pigment filler. The anti-corrosion coating prepared by the present invention has good corrosion resistance and weather resistance; the modified microcapsules use modified fluorescent materials and anthocyanins as core materials, and utilize the modified fluorescent materials and metal ions generated after encountering substrate corrosion to produce fluorescence effects. Anthocyanins are a pH-sensitive material. When it is acidic, the aqueous solution is red; under neutral conditions, anthocyanins are mainly colorless methanol pseudobases in the solution; when the pH is alkaline, anthocyanins mainly appear as blue quinone bases. When the pH value of the local environment changes, anthocyanins achieve different color changes, thereby preparing a coating based on fluorescence-induced corrosion with dual warning.
[0039] 2. (4-aminophenyl)(phenyl)methanone[(4-aminophenyl)(phenyl)methylene]hydrazone and 4'-(4-formylphenyl)-2,2':6',2"-terpyridine are both aromatic fused ring compounds with large planar and rigid structures and large conjugated systems, and both have high fluorescence quantum efficiency; (4-aminophenyl)(phenyl)methanone[(4-aminophenyl)(phenyl)methylene]hydrazone and 4'-(4-formylphenyl)-2,2':6',2"-terpyridine The combination with 4'-(4-formylphenyl)-2,2':6',2"-terpyridine helps to expand the conjugated π bond of the intermediate A molecule and the delocalization range of the electrons, thereby easily exciting it into a high-energy excited state molecule, further improving the fluorescence intensity and fluorescence sensitivity; in addition, the three pyridine nitrogens on 4'-(4-formylphenyl)-2,2':6',2"-terpyridine all have lone pairs of electrons and have strong electron-donating ability, which can complex with metal ions and further detect the presence of trace metal ions as an indicator of corrosion.
[0040] 3. The intermediate A is further restricted in rotation of the outer benzene ring and molecular vibration through chlorination, formylation and further cyano modification, thereby improving its own fluorescence quantum efficiency; in addition, the introduced cyano functional group can further improve its own composite ability with the core material component anthocyanin and the wall material component, and further improve the overall stability of the microcapsule; anthocyanin has different color changes under different pH conditions, and external factors (such as light, heat, oxygen, etc.) will affect the stability of anthocyanin, thereby limiting its scope of application, so using suitable materials to embed anthocyanin into microcapsules and isolate anthocyanin from the external environment can more effectively improve the stability of anthocyanin. DETAILED DESCRIPTION
[0041] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Example 1
[0043] This embodiment provides a method for preparing a modified fluorescent material for a coating based on fluorescence-induced corrosion, comprising the following steps:
[0044] B1. Add 15 g of (4-aminophenyl)(phenyl)methanone [(4-aminophenyl)(phenyl)methylene]hydrazone, 15 g of 4'-(4-formylphenyl)-2,2':6',2"-terpyridine and 300 mL of ethanol into a 500 mL three-necked flask, and add a magnet into the three-necked flask; then condense and reflux the three-necked flask at 70°C and 100 r / min for 4 h, and then filter while hot to obtain a modified solid. The modified solid was alternately washed with ethanol and deionized water, and then vacuum dried in a vacuum drying oven at 70°C for 30 min to obtain intermediate A.
[0045] B2, 20g of intermediate A is added to a 250mL four-necked flask, and a thermometer, a chlorine tube and a stirrer are inserted into the four necks respectively, and an external electric heating jacket is installed; 0.1g of catalyst ferric chloride is added to the four-necked flask, mixed evenly, and then chlorine gas is introduced until the four-necked flask is filled with chlorine gas. The four-necked flask is then heated to 60°C and reacted for 1h to obtain a solid; the solid is cooled to room temperature to obtain chlorinated intermediate A.
[0046] B3. Add 1 g of chlorinated intermediate A into a 50 mL four-necked round-bottom flask, add 30 mL of anhydrous tetrahydrofuran under a nitrogen atmosphere, and mix and stir evenly; transfer the four-necked round-bottom flask to a cold water bath, then drop 10 mL of liquid n-butyl lithium and 20 mL of DMF, stir at 100 r / min for 40 min, and extract to obtain an organic phase; the organic phase is washed with saturated brine, dried over anhydrous sodium sulfate, and filtered to obtain intermediate B.
[0047] B4. In a 100mL four-necked round-bottom flask, add 30mL of ethanol solution, 1g of benzyl cyanide and 1.5g of potassium tert-butoxide, mix and stir evenly at room temperature, then add 3g of intermediate B, mix and stir evenly to obtain a mixed solid-liquid; heat the mixed solid-liquid to 70°C and reflux for 3h, then cool to room temperature and separate to obtain an organic phase; use petroleum ether and ethyl acetate as solvents for elution of the organic phase to obtain a modified fluorescent material.
[0048] Example 2
[0049] This embodiment provides a method for preparing a modified fluorescent material for a coating based on fluorescence-induced corrosion, comprising the following steps:
[0050] B1. Add 18 g of (4-aminophenyl)(phenyl)methanone [(4-aminophenyl)(phenyl)methylene]hydrazone, 20 g of 4'-(4-formylphenyl)-2,2':6',2"-terpyridine and 300 mL of ethanol into a 500 mL three-necked flask, and add a magnet into the three-necked flask; then condense and reflux the three-necked flask at 75°C and 200 r / min for 4.5 h, and then filter while hot to obtain a modified solid; wash the modified solid alternately with ethanol and deionized water, and then vacuum dry it in a vacuum drying oven at 75°C for 40 min to obtain intermediate A.
[0051] B2, 25g of intermediate A is added to a 250mL four-necked flask, and a thermometer, a chlorine tube and a stirrer are inserted into the four necks respectively, and an external electric heating jacket is installed; 1g of catalyst ferric chloride is added to the four-necked flask, mixed evenly, and then chlorine gas is introduced until the four-necked flask is filled with chlorine gas. The four-necked flask is then heated to 66°C and reacted for 1.5h to obtain a solid; the solid is cooled to room temperature to obtain chlorinated intermediate A.
[0052] B3. Add 3 g of chlorinated intermediate A into a 50 mL four-necked round-bottom flask, add 36 mL of anhydrous tetrahydrofuran under a nitrogen atmosphere, and mix and stir evenly; transfer the four-necked round-bottom flask to a cold water bath, then drop 15 mL of liquid n-butyl lithium and 24 mL of DMF, stir at 100 r / min for 40 min, and extract to obtain an organic phase; the organic phase is washed with saturated brine, dried over anhydrous sodium sulfate, and then filtered to obtain intermediate B.
[0053] B4. In a 100mL four-necked round-bottom flask, add 30mL of ethanol solution, 1.5g of benzyl cyanide and 2g of potassium tert-butoxide, mix and stir at room temperature, then add 4g of intermediate B, mix and stir evenly to obtain a mixed solid-liquid; heat the mixed solid-liquid to 75°C and reflux for 3.6h, then cool to room temperature and separate to obtain an organic phase. The organic phase is eluted with petroleum ether and ethyl acetate to obtain a modified fluorescent material.
[0054] Example 3
[0055] This embodiment provides a method for preparing a modified fluorescent material for a coating based on fluorescence-induced corrosion, comprising the following steps:
[0056] B1. Add 20 g of (4-aminophenyl)(phenyl)methanone [(4-aminophenyl)(phenyl)methylene]hydrazone, 25 g of 4'-(4-formylphenyl)-2,2':6',2"-terpyridine and 300 mL of ethanol into a 500 mL three-necked flask, and add a magnet into the three-necked flask; then condense and reflux the three-necked flask at 80°C and 300 r / min for 5 h, and then filter while hot to obtain a modified solid. The modified solid is washed alternately with ethanol and deionized water, and then vacuum dried in a vacuum drying oven at 80°C for 60 min to obtain intermediate A.
[0057] B2, 30g of intermediate A is added to a 250mL four-necked flask, and a thermometer, a chlorine tube and a stirrer are inserted into the four necks respectively, and an external electric heating jacket is installed; 1g of catalyst ferric chloride is added to the four-necked flask, mixed evenly, and then chlorine gas is introduced until the four-necked flask is filled with chlorine gas. The four-necked flask is then heated to 70°C and reacted for 2h to obtain a solid; the solid is cooled to room temperature to obtain chlorinated intermediate A.
[0058] B3. Add 5 g of chlorinated intermediate A into a 50 mL four-necked round-bottom flask, add 40 mL of anhydrous tetrahydrofuran under a nitrogen atmosphere, and mix and stir evenly; transfer the four-necked round-bottom flask to a cold water bath, then drop 20 mL of liquid n-butyl lithium and 30 mL of DMF, stir at 100 r / min for 40 min, and extract to obtain an organic phase; the organic phase is washed with saturated brine, dried over anhydrous sodium sulfate, and then filtered to obtain intermediate B.
[0059] B4. In a 100mL four-necked round-bottom flask, add 30mL of ethanol solution, 2g of benzyl cyanide and 3g of potassium tert-butoxide, mix and stir evenly at room temperature, then add 5g of intermediate B, mix and stir evenly to obtain a mixed solid-liquid; heat the mixed solid-liquid to 80°C and reflux for 4h, then cool to room temperature and separate to obtain an organic phase. The organic phase is eluted with petroleum ether and ethyl acetate to obtain a modified fluorescent material.
[0060] Example 4
[0061] This embodiment provides a method for preparing modified microcapsules for coatings based on fluorescence-induced corrosion, comprising the following steps:
[0062] Step 1: Preparation of modified microcapsules
[0063] A1. Mix 10 g of the modified fluorescent material prepared in Example 1, 5 g of anthocyanin, 0.2 g of Span85 and 20 mL of deionized water, place in a 50° C. water bath, and stir at 100 rpm for 10 min to obtain a mixed solution; perform ultrasonic emulsification on the mixed solution to obtain a core material emulsion. The power of ultrasonic emulsification of the mixed solution is 30 W, and the duration of ultrasonic emulsification is 10 min.
[0064] A2. Mix 5 g of β-cyclodextrin, 5 g of gum arabic and 20 mL of deionized water, and stir magnetically at 70° C. and 300 rpm until the mixed solution becomes transparent to obtain a wall material solution.
[0065] A3. Add 20 mL of wall material solution drop by drop into 10 mL of core material emulsion, disperse under high-speed dispersing homogenizer after stirring, and then stand to defoam; after defoaming, spray dry to obtain modified microcapsules. The inlet air temperature of spray drying is 180℃ and the wind speed is 100m 3 / h.
[0066] Example 5
[0067] This embodiment provides a method for preparing modified microcapsules for coatings based on fluorescence-induced corrosion, comprising the following steps:
[0068] Step 1: Preparation of modified microcapsules
[0069] A1. Mix 16 g of the modified fluorescent material prepared in Example 2, 8 g of anthocyanin, 0.4 g of Span85 and 20 mL of deionized water, place in a water bath at 53°C, and stir at 130 rpm for 18 min to obtain a mixed solution; perform ultrasonic emulsification on the mixed solution to obtain a core material emulsion. The power of ultrasonic emulsification of the mixed solution is 40 W, and the duration of ultrasonic emulsification is 16 min.
[0070] A2. Mix 5 g of β-cyclodextrin, 5 g of gum arabic and 20 mL of deionized water, and stir magnetically at 450 rpm at 74° C. until the mixed solution becomes transparent to obtain a wall material solution.
[0071] A3. Add 26 mL of wall material solution drop by drop into 10 mL of core material emulsion, disperse under high-speed dispersing homogenizer after stirring, and then stand to defoam; after defoaming, spray dry to obtain modified microcapsules. The inlet air temperature of spray drying is 185°C and the wind speed is 110m / s. 3 / h.
[0072] Example 6
[0073] This embodiment provides a method for preparing modified microcapsules for coatings based on fluorescence-induced corrosion, comprising the following steps:
[0074] Step 1: Preparation of modified microcapsules
[0075] A1. Mix 20 g of the modified fluorescent material prepared in Example 3, 10 g of anthocyanin, 0.5 g of Span85 and 20 mL of deionized water, place in a 60°C water bath, and stir at 200 rpm for 20 min to obtain a mixed solution; perform ultrasonic emulsification on the mixed solution to obtain a core material emulsion. The power of ultrasonic emulsification of the mixed solution is 50 W, and the duration of ultrasonic emulsification is 20 min.
[0076] A2. Mix 5 g of β-cyclodextrin, 5 g of gum arabic and 20 mL of deionized water, and stir magnetically at 80° C. and 500 rpm until the mixed solution becomes transparent to obtain a wall material solution.
[0077] A3. Add 30 mL of wall material solution drop by drop into 10 mL of core material emulsion, disperse under high-speed dispersing homogenizer after stirring, and then stand to defoam; after defoaming, spray dry to obtain modified microcapsules. The inlet air temperature of spray drying is 200℃ and the wind speed is 120m / s. 3 / h.
[0078] Example 7
[0079] This embodiment provides a method for preparing modified microcapsules for coatings based on fluorescence-induced corrosion, comprising the following steps:
[0080] S1. Mix 150 parts of epoxy resin E5, 20 parts of modified microcapsules prepared in Example 4, 2 parts of silane coupling agent, 0.5 parts of tristearate and 1.5 parts of hydrogenated castor oil, and disperse them evenly using a high-speed disperser to obtain component A.
[0081] S2, 20 parts of epoxy curing agent K123 and 10 parts of cardanol glycidyl ether were mixed evenly, and then 5 parts of zinc phosphate and 5 parts of ferrophosphorus powder were added, and dispersed evenly using a high-speed disperser to obtain component B; component A was added to component B and dispersed evenly to obtain a coating based on fluorescent induction corrosion.
[0082] Example 8
[0083] This embodiment provides a method for preparing a coating based on fluorescence-induced corrosion, comprising the following steps:
[0084] S1. Mix 150 parts of epoxy resin E5, 17 parts of modified microcapsules prepared in Example 5, 1 part of silane coupling agent, 0.3 parts of ethyl bisstearamide and 1.2 parts of hydrogenated castor oil, and disperse them evenly using a high-speed disperser to obtain component A.
[0085] S2, 18 parts of epoxy curing agent T-31 and 6 parts of cardanol glycidyl ether were evenly mixed, and then 2.5 parts of zinc phosphate and 2.5 parts of ferrophosphorus powder were added and dispersed evenly using a high-speed disperser to obtain component B; component A was added to component B and evenly dispersed to obtain a coating based on fluorescent induction corrosion.
[0086] Example 9
[0087] This embodiment provides a method for preparing a coating based on fluorescence-induced corrosion, comprising the following steps:
[0088] S1. Mix 450 parts of epoxy resin E4, 20 parts of modified microcapsules prepared in Example 6, 2 parts of silane coupling agent, 0.5 parts of glyceryl stearate and 1.5 parts of hydrogenated castor oil, and disperse them evenly using a high-speed disperser to obtain component A.
[0089] S2, 59320 parts of epoxy curing agent and 10 parts of cardanol glycidyl ether are mixed evenly, and then 3 parts of zinc phosphate and 3 parts of ferrophosphorus powder are added and dispersed evenly using a high-speed disperser to obtain component B; component A is added to component B and dispersed evenly to obtain a coating based on fluorescent induction corrosion.
[0090] Comparative Example 1
[0091] The difference between this comparative example and Example 3 is that step B3 and step B4 are omitted, and intermediate A is the prepared modified fluorescent material.
[0092] Comparative Example 2
[0093] The difference between this comparative example and Example 9 is that in step S1, no modified microcapsules are added to component A.
[0094] Performance Test 1: The modified fluorescent materials prepared in Examples 1-3 were irradiated with a UV-B lamp at a light intensity of 0.6 W / m 2 The irradiation time is 10h, and its glossiness is tested.
[0095] The test results are shown in Table 1:
[0096] Table 1
[0097]
[0098] Data Analysis:
[0099] The glossiness of the modified fluorescent materials prepared in Examples 1-3 and Comparative Example 1 was tested. The modified fluorescent materials prepared in Examples 1-3 were all highly sensitive to light sources. In Comparative Example 1, since the modified fluorescent material was not modified with a functional group, the rotation of the outer benzene ring was not restricted, which reduced its own fluorescence quantum efficiency, which was manifested as a decrease in the glossiness value.
[0100] Performance Test 2: The fluorescent induction corrosion-based coatings prepared in Examples 7-9 and Comparative Example 2 were placed in a can and stored in a constant temperature environment of 50° C. to observe whether the coatings had precipitation.
[0101] According to GB / T 10125-201 "Artificial atmosphere corrosion test salt spray test", the coatings based on fluorescence induction corrosion prepared in Examples 7-9 and Comparative Example 2 were subjected to salt spray resistance test. The coating based on fluorescence induction corrosion was applied to the surface of the steel plate with a coating thickness of 300 μm, and the time when bubbling and rusting occurred was recorded.
[0102] The specific test results are shown in the table below:
[0103] Table 2
[0104]
[0105] Data Analysis:
[0106] The storage stability and corrosion resistance of the coatings based on fluorescence induction corrosion prepared in Examples 7-9 and Comparative Example 1 were tested at 50°C, indicating that the modified microcapsules prepared in Examples 4-6 of the present invention and the coatings based on fluorescence induction corrosion prepared in Examples 7-9 all have good stability and corrosion resistance.
[0107] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0108] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0109] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a coating based on fluorescence-induced corrosion, characterized in that: The following steps are involved: S1, epoxy resin, modified microcapsules, silane coupling agent, dispersant and thixotropic agent are uniformly mixed to obtain component A; S2, epoxy resin curing agent and active diluent are mixed evenly, and then pigments and fillers are added and dispersed evenly at high speed to obtain component B; component A is added to component B and dispersed evenly to obtain a coating based on fluorescent induction corrosion; The preparation method of the modified microcapsule comprises the following steps: A1. Evenly mix the modified fluorescent material, anthocyanin, Span85 and deionized water, and stir at 50-60° C. for 10-20 min to obtain a mixed solution; ultrasonically emulsify the mixed solution to obtain a core material emulsion; A2, β-cyclodextrin, gum arabic and deionized water are mixed uniformly to obtain a mixed solution; the mixed solution is magnetically stirred at 70-80° C. and 300-500 rpm until the mixed solution becomes transparent to obtain a wall material solution; A3, adding the wall material solution drop by drop into the core material emulsion, uniformly dispersing it under a high-speed dispersing homogenizer, and then standing to defoam to obtain a mixed solution; spray drying the mixed solution to obtain modified microcapsules; In step A1, the usage ratio of modified fluorescent material, anthocyanin, Span85 and deionized water is 10-20 g: 5-10 g: 0.2-0.5 g: 20 mL; the power of ultrasonic emulsification is 30-50 W, and the duration of ultrasonic emulsification is 10-20 min; In step A2, the dosage ratio of β-cyclodextrin, gum arabic and deionized water is 5g:5g:20mL; in step A3, the dosage ratio of wall material solution and core material emulsion is 20-30mL:10mL; the inlet air temperature of spray drying is 180-200℃ and the wind speed is 100-120m 3 / h; In step A1, the preparation method of the modified fluorescent material comprises the following steps: B1. Mix (4-aminophenyl)(phenyl)methanone [(4-aminophenyl)(phenyl)methylene]hydrazone, 4'-(4-formylphenyl)-2,2':6',2"-terpyridine and ethanol evenly, condense and reflux at 70-80°C and 100-300r / min for 4-5h, and filter while hot to obtain a modified solid; wash the modified solid alternately with ethanol and deionized water, and then vacuum dry to obtain intermediate A; B2, intermediate A, and catalyst ferric chloride are mixed to obtain a reactant; chlorine gas is introduced into the reactant to prepare a chlorinated intermediate A; B3, under nitrogen atmosphere, add anhydrous tetrahydrofuran to the chlorinated intermediate A, mix and stir evenly to obtain a mixed solid-liquid; n-butyl lithium and anhydrous DMF are added dropwise to the mixed solid-liquid, and the temperature is cooled to room temperature to obtain a reaction solution; saturated ammonium chloride solution is added to the reaction solution, extracted to obtain an organic phase; the organic phase is washed with saturated brine, dried over anhydrous sodium sulfate, and filtered to obtain intermediate B; B4, ethanol solution, benzyl cyanide and potassium tert-butoxide are mixed, stirred at room temperature, and then intermediate B is added, mixed and stirred evenly to obtain a mixed solid-liquid; the mixed solid-liquid is heated to 70-80° C. and refluxed for 3-4 hours, then cooled to room temperature, and separated to obtain an organic layer; the organic layer is concentrated under reduced pressure, and the crude product is passed through a silica gel column, and purified using petroleum ether and ethyl acetate as eluting solvents to obtain a modified fluorescent material; In step B1, the amount ratio of (4-aminophenyl)(phenyl)methanone[(4-aminophenyl)(phenyl)methylene]hydrazone, 4'-(4-formylphenyl)-2,2':6',2"-terpyridine and ethanol is 15-20g:15-25g:300mL; the vacuum drying temperature is 70-80°C, and the vacuum drying time is 30-60min; In step B2, the ratio of intermediate A to catalyst ferric chloride is 20 g:0.1-0.3 g, the temperature of the mixed reaction is 60-70° C., and the duration of the mixed reaction is 1-2 h; In step B3, the amount ratio of chlorinated intermediate A, anhydrous tetrahydrofuran, n-butyl lithium and anhydrous DMF is 10-15g:50-60mL:10-20mL:30-40mL; in step B4, the amount ratio of ethanol solution, benzyl cyanide, potassium tert-butoxide and intermediate B is 10-20mL:60mg:30mg:20-30mg.
2. A method for preparing a coating based on fluorescence-induced corrosion according to claim 1, characterized in that: In step S1, the epoxy resin is any one of epoxy resin E51 and epoxy resin E44, and their combinations; the dispersant is any one of ethyl bis stearamide, glyceryl stearate, and glyceryl tristearate, and their combinations; the thixotropic agent is any one of hydrogenated castor oil and polyvinyl alcohol, and their combinations; the epoxy resin curing agent is any one of epoxy curing agent T-31, epoxy curing agent 593, and epoxy curing agent K123, and their combinations; and the active diluent is cardanol glycidyl ether.
3. The method for preparing a coating based on fluorescence-induced corrosion according to claim 1, characterized in that: In parts by weight, the usage ratio of epoxy resin, modified microcapsules, silane coupling agent, dispersant and thixotropic agent is 50:10-20:1-2:0.1-0.5:1-1.5; in parts by weight, the usage ratio of epoxy resin curing agent, active diluent and pigments and fillers is 10-20:5-10:5-10; the pigments and fillers are zinc phosphate and ferrophosphorus powder, and in parts by weight, the usage ratio of zinc phosphate and ferrophosphorus powder is 1:1.
Citation Information
Patent Citations
Fluorescent paint doped with organic-inorganic composite fluorescent montmorillonoid and preparation method of fluorescent paint
CN107793817A
PH value sensitive micro capsule as well as preparation method and application thereof
CN112354493A
Microcapsule-based multifunctional coating and application thereof
CN114921156A
Preparation method of beta-cyclodextrin purple sweet potato anthocyanin microcapsule
CN115089729A